Galantamine Attenuates Aluminum Chloride-Induced Cytotoxicity and Modulates Tumor Necrosis Factor Expression in SH-SY5Y Cells - Mahmoud, Luma Ali; Rana Ayad Ghaleb; Aymen A. Bash (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Neuroinflammation and oxidative stress are central to Alzheimer's disease pathogenesis. Aluminum chloride (AlCl₃) is a neurotoxicant utilized to model these pathological features, whereas galantamine, a clinically approved therapeutic, exhibits secondary anti-inflammatory properties. To evaluate the protective efficacy of galantamine against AlCl₃-induced cytotoxicity and its modulatory impact on tumor necrosis factor (TNF) gene expression in human neuroblastoma cells. Methods: SH-SY5Y cells were exposed to varying concentrations of AlCl₃ or galantamine for 24 hours. For combination treatments, cells were pretreated with galantamine prior to AlCl₃ exposure. Cellular viability was evaluated using the MTT assay, and relative TNF mRNA expression was quantified via RT-qPCR. Results: High-dose AlCl₃ (500 µg/mL) significantly decreased cell viability to 65% and upregulated TNF expression by 2.3-fold (p<0.001). Pretreatment with galantamine (100 µg/mL) partially restored cell viability (88–95%) and significantly suppressed the AlCl₃-induced TNF overexpression to 0.36-fold of control levels (p<0.001). Conclusion: Galantamine confers neuroprotection against metal-induced cellular injury by downregulating pro-inflammatory signaling cascades. These findings highlight its potential therapeutic utility in mitigating neuroinflammation-driven neurodegenerative processes beyond its primary cholinergic action.